The Analysis of the Attention Levels of 10-12 Aged Children Playing Fencing - Reşat Kartal; Çağatay Dereceli; Alper Kartal (ümit doğan üstün, 2016)
The purpose of this study was to investigate whether the fencing exercises effect the attention level of the children at the age of 12-14. The sampling group of the study was consisted of 40 children of whom 20 were athletes of Göztepe Sport Club Fencing Team and 20 were students of Aydın Efeler Middle School. Bourdon attention test was applied to both experimental and control group. The SPSS statistical program (version 20.0) was used for data analysis. Independent-samples t-tests and one way Anova were used to determine significant differences. A significant difference was found between experimental and control group participated in the study (p<0.05). As a result attention values of students who do fencing was found to be higher than who does not. In this context we can say fencing exercise help children's attention level who lacks of attention.